Experimental Study of Two Impinging Jets Aligned With a Crossflow - Barata, Jorge M M (2022)
Laser Doppler measurements provide information on the flowfield created by twin impinging jets aligned with a low velocity crossflow. The experiments were carried out for a Reynolds number based on the jet exit conditions of Rej = 4.3 × 104, an impingement height of 20.1 jet diameters and for a velocity ratio between the jet exit and the crossflow VR = Vj/Uo of 22.5, and an inter-jet spacing of S = 6D. The results show a large penetration of the first (upstream) jet that is deflected by the crossflow and impinges on the ground, giving rise to a ground vortex due to the collision of the radial wall and the crossflow that wraps around the impinging point like a scarf. The second jet (located downstream) is not so affected by the crossflow in terms of deflection, but due to the downstream wall jet that flows radially from the impinging point of the first jet it does not reach the ground. The results indicate a new flow pattern not yet reported so far, that is most relevant for a VSTOL aircraft operating in ground vicinity with front wind or small forward movement may result in enhanced under pressures in the aft part of the aircraft causing a suction down force and a change of the pitching moment towards the ground.